A Model for Reducing Anger Through the Cultivation of Loving-Kindness Among Senior High School Students - Pavarissaro, Pavaris (Mahachula Academic Journal, 2025)
The objectives of this research are 1) To study the state of anger (tosacharit) in the minds of high school students and their practice of Buddhist principles that lead to reducing anger and increasing compassion. 2) To analyze lessons and changes resulting from applying compassion principles in reducing anger among high school students. 3) To propose a model for reducing anger through cultivating compassion among high school students. This research is an action research employing a mixed-methods approach, incorporating both quantitative and qualitative methods. The participants consisted of 46 upper secondary school students over a period of five days. The data collection tools included questionnaires, interviews, focus group discussions, and activities aimed at reducing dishonesty based on the principle of cultivating loving-kindness. The data were analyzed using content analysis and statistical methods, including percentage, mean, and standard deviation, along with descriptive and content-based analytical summaries. The research results found that : The study found that anger (or tosa-jariya) in high school students stems from attachment to the self and things they value. When these are threatened—physically, verbally, or emotionally—it leads to dissatisfaction and anger. Practicing loving-kindness (metta) through physical actions, speech, and thoughts helps calm the mind, improves relationships, reduces anger, and supports students' mental well-being. The analysis revealed that teaching the principles of loving-kindness significantly reduced anger and enhanced emotional intelligence in students. The overall pre- and post-activity scores differed significantly by 2.523 (p = 0.002). Female students showed a greater significant improvement (3.385, p = 0.004), while male students also improved (1.874), but the change was not statistically significant (p = 0.183). Most students extended loving-kindness to benefactors and close individuals, while fewer expressed unconditional loving-kindness at a higher moral level. This indicates that the practice of loving-kindness still depends on situational and environmental factors. The model for reducing anger (tosa-jariya) through the cultivation of loving-kindness among high school students is called the “BSEP” model, which consists of four key components : 1) B (Buddha’s Dhamma) – The teachings of the Buddha: This involves practicing loving-kindness through actions such as giving alms, offering food to monks, helping animals, and sharing belongings. These practices help reduce anger and foster a compassionate mindset. 2) S (Smile) – Creating a pleasant atmosphere: This includes using polite language, speaking kindly, and offering comfort to others. Such behaviors promote a positive environment, reduce anger, and enhance happiness. 3) E (Emotion) – Emotional regulation: This component focuses on developing awareness of anger, analyzing its causes, and training in positive emotional management. 4) P (Positive Thinking) – Developing a positive mindset: Encouraging optimistic thinking to build inner strength and reduce negative emotions.